The explanation of preference of the youth decision on the choices between UiTM and IKM as a platform for a better future / Mohd Ilham Yusop and Matfazly Mat Kasim - Yusop, Mohd Ilham; Mat Kasim, Matfazly (2013)
The research explains on the factors that influence decision making made among the youth in the rural area that comes from poor family and possess average SPM result in between the choosing of UiTM and IKM. The research is based on qualitative method as the interview with the administrator of the program was taken as the subject of justification. The quantitative method used is to confirm the findings quantitatively. Among the factors discussed in the research paper are benefit, risk, interest, knowledge, environment, economy and policy which are constructed by the researchers. The factors described also represent the internal factor and the external factors. The factors will be used to determine the enrolment success of UiTM and IKM respectively. As qualitative measure, researchers will analyse the findings from the horse's mouth of each program respectively as well to see the alignment of rural youth towards each institution. IKM is used to be the benchmark of the enrolment success as it's managed to fulfill its quota for its annual intake as well as to represent the vocational education. The UiTM findings determine the rural youth alignment towards academic oriented education. The comparison between UiTM and IKM influencing factors will be discussed and used for the purpose of recommendation on the UiTM enrolment success.